A method for modifying the interface of carbon fiber reinforced thermoplastic resin-based composite materials

By forming chemical bond connections at the interface between carbon fiber and polymethyl methacrylate resin, the problem of insufficient bonding force between carbon fiber and thermoplastic resin matrix is ​​solved, and the mechanical properties of the composite material are significantly improved and its application range is broadened.

CN116039120BActive Publication Date: 2025-01-17QINGDAO UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310066402.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-16
Publication Date
2025-01-17
Estimated Expiration
2043-01-16

AI Technical Summary

Technical Problem

The interface bonding force between carbon fiber and thermoplastic resin matrix is ​​insufficient, resulting in the failure of the mechanical properties of fiber-reinforced thermoplastic composite materials to fully exert, affecting their bearing capacity.

Method used

Hexamethylene diisocyanate is used as the intermediate coupling layer, and carboxylic groups are introduced by oxidizing the carbon fiber surface through acid potassium permanganate solution, and polymethyl methacrylate is partially hydrolyzed by tetrahydrofuran and hydrochloric acid to form a functionalized resin with carboxylic groups to form Chemical bonding with fibers and resins to improve interface bonding performance.

Benefits of technology

The interface bonding force between carbon fiber and polymethyl methacrylate resin is enhanced through chemical grafting, which significantly improves the mechanical properties of the composite material and broadens its application range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116039120B_ABST
    Figure CN116039120B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for modifying the interface of a carbon fiber reinforced thermoplastic resin-based composite material. The method improves the mechanical properties of the interface of the fiber reinforced thermoplastic resin-based composite material by grafting the surface of the material. The interface of carbon fiber (CF) and polymethyl methacrylate resin (PMMA) is modified, and an active group carboxyl group is introduced on the surface of the material. Then, hexamethylene diisocyanate (HDI) is used as a coupling layer to connect the carboxyl groups on the surface of the carbon fiber and the polymethyl methacrylate resin to form a "molecular bridge" to enhance the interface bonding force between the resin and the fiber by chemical grafting. A modified carbon fiber reinforced polymethyl methacrylate composite material sample (CF / PMMA) is prepared by a thin film lamination method, and a microscopic verification test is performed on the prepared composite material sample to verify the effectiveness of the method proposed by the present invention, so as to lay a foundation for the wide application of fiber reinforced thermoplastic resin-based composite materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of manufacturing for improving the interface performance of composite materials, and in particular relates to an interface modification process of a carbon fiber reinforced thermoplastic resin-based composite material. Background Art

[0002] As a commonly used material for enhancing the strength of resin-based composite materials, carbon fiber has excellent mechanical properties such as high strength, high modulus, and low density. Its special hexagonal atomic structure arrangement also gives carbon fiber good electrical and thermal conductivity and stable chemical properties. Carbon fiber reinforced thermoplastic and thermosetting resin-based composite materials have been widely used in aerospace, high-speed trains and other fields.

[0003] Compared with thermoplastic resin-based composites, thermosetting resin-based composites have disadvantages such as low damage tolerance, long processing cycle, and difficulty in recycling, so their application areas are limited to a certain extent. Thermoplastic resin-based composites have the advantages of high damage tolerance, convenient processing, and waste can be re-melted and reused, so they have become a hot spot for development in the field of composite material research.

[0004] Since the surface of carbon fiber is smooth and has few polar groups, it is chemically inert as a whole and has poor interfacial bonding ability with the thermoplastic resin matrix. Therefore, improving the interfacial bonding between carbon fiber and thermoplastic resin matrix has become a key research issue. A lot of research has been done by predecessors on improving the interfacial properties of thermoplastic resin and carbon fiber. The main methods adopted are surface modification of carbon fiber, such as electrodeposition, chemical etching, water solvent thermal method, sizing method and plasma treatment. The characteristics of these methods are that they do not fundamentally solve the problem of insufficient interfacial bonding between carbon fiber and thermoplastic resin matrix. After being stressed, the carbon fiber is easily extracted from the resin matrix, resulting in the mechanical properties of the reinforcement phase not being fully exerted, thereby seriously affecting the bearing capacity of the entire fiber reinforced thermoplastic composite material. Summary of the invention

[0005] The purpose of the present invention is to overcome the deficiencies of the above-mentioned prior art and provide a method for improving the interface mechanical properties of carbon fiber reinforced polymethyl methacrylate composite materials, that is, the present invention bidirectionally modifies the carbon fiber and the resin, and uses hexamethylene diisocyanate (HDI) as an intermediate coupling layer to form a chemical bond connection between the fiber and the resin interface, so that the fiber and the resin are grafted into a whole, effectively improving the interface bonding performance.

[0006] To achieve the above purpose, the technical process scheme adopted by the present invention is:

[0007] A process for improving the interface mechanical properties of carbon fiber reinforced polymethyl methacrylate composite materials, the method steps comprising:

[0008] 1) Prepare an acidic potassium permanganate solution, immerse the cleaned carbon fiber in the prepared acidic potassium permanganate solution, take out the carbon fiber after soaking for a set time, clean and dry it, and seal it for storage;

[0009] 2) Brush tetrahydrofuran on the surface of the cleaned polymethyl methacrylate film, seal it and let it stand, then take it out, and then soak it in a dilute hydrochloric acid solution for a set time. After the treatment, take it out, dry it, seal it and store it for later use;

[0010] 3) cutting the processed polymethyl methacrylate film and carbon fiber into appropriate sizes according to the size of the mold;

[0011] 4) Apply a layer of hexamethylene diisocyanate on the surface of the processed and cut fibers and resin films, apply evenly, and lay them in the designed laying order to form a preform, so that the outermost layers of the upper and lower surfaces of the preform are both resin film sheets;

[0012] 5) Lay release cloth on the upper and lower surfaces of the preform, and then put it into a vacuum bag for vacuum treatment;

[0013] 6) The vacuumed and treated composite material preform is placed in a press molding mold with a set temperature and a set pressure. After hot pressing for a set time, the mold is taken out and placed on a workbench to cool. After cooling to room temperature, the demolding cloth is opened to obtain a modified carbon fiber reinforced polymethyl methacrylate composite material sample.

[0014] As a further technical solution, the acidic potassium permanganate solution described in step 1) is a mixed solution prepared by using deionized water with a mass fraction of 5 to 30% and adding an appropriate amount of dilute hydrochloric acid with a concentration of 0.01 to 1 mol / L. Potassium permanganate, as a common strong oxidant, has the strongest oxidizing property under acidic conditions and will not damage the surface structure of the material. Under the oxidation of the acidic potassium permanganate solution, carboxyl groups appear on the surface of the carbon fiber.

[0015] As a further technical solution, the immersion process described in step 1) is carried out in an ultrasonic cleaner with a water bath temperature of 10 to 60°C.

[0016] As a further technical solution, the method for cleaning and drying the carbon fiber in step 1) is to wash the surface of the carbon fiber four times with deionized water, and put the cleaned carbon fiber into a preheated oven for drying for 10 to 50 minutes.

[0017] As a further technical solution, the purpose of using tetrahydrofuran to treat the surface of the resin sheet in step 2) is that polymethyl methacrylate can be dissolved by tetrahydrofuran, and after partially dissolving the surface of the film sheet, it can better react with hydrochloric acid to generate polar group carboxyl.

[0018] As a further technical solution, the concentration of the hydrochloric acid solution used in step 2) is 0.01 to 1 mol / L.

[0019] As a further technical solution, the soaking process described in step 2) is carried out in an oven with an internal temperature of 10 to 60°C.

[0020] As a further technical solution, the purpose of using the hexamethylene diisocyanate as an intermediate medium in step 4) is that both ends of the hexamethylene diisocyanate molecule have polar -NCO groups, which can chemically react with the carboxyl groups on the fiber and the resin respectively, connecting the two materials well and realizing chemical grafting.

[0021] The working principle of the present invention is as follows:

[0022] Hexamethylene diisocyanate (HDI) has polar -NCO groups at both ends of the molecular chain. Based on this special molecular structure, HDI is used as an intermediate medium to connect the fiber and resin interface. After the fiber and resin surface are modified, -COOH groups are introduced on the material surface, which react with the -NCO polar groups at both ends of HDI to form a chemical bond connection between the composite material bonding interface. The chemical reaction formula is:

[0023] R-NCO+R′-COOH→R-NH-COR′+CO2.

[0024] The implementation effects of the present invention are as follows:

[0025] The present invention is different from the traditional film lamination method for making CF / PMMA composite materials, and proposes a new method for improving the interface bonding performance of the material. The traditional film lamination method for making CF / PMMA composite materials is simply to heat the resin to a molten state and then physically bond it to the carbon fiber. The interface bonding force is low, and thus it cannot be widely used. The present invention is to first oxidize the carbon fiber with an acidic potassium permanganate solution to introduce carboxyl groups on the fiber surface; secondly, use tetrahydrofuran and hydrochloric acid solution to hydrolyze part of the ester groups on the surface of polymethyl methacrylate to generate a functionalized resin with carboxyl groups; finally, hexamethylene diisocyanate is coated on the surface of the modified fiber and resin film, and the polar -NCO functional groups (such as Figure 1 The carboxyl groups on the resin and the fiber are connected to form a "molecular bridge", which realizes chemical grafting between the resin and the fiber, making the interlayer performance of the CF / PMMA composite material better and broadening the practical application range of fiber-reinforced thermoplastic resin-based composite materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 Shown is the HDI molecular structure model;

[0027] Figure 2The figure shows the principle of CF / PMMA grafting between HDI layers;

[0028] Figure 3 Shown is a schematic diagram of the laying sequence of CF and PMMA;

[0029] Figure 4 shows the FTIR spectra of CF and PMMA at each treatment stage;

[0030] Figure 5 shows the SEM surface morphology before and after CF modification treatment;

[0031] Figure 6 shows the SEM surface morphology of PMMA before and after modification;

[0032] Figure 7 Shown is the SEM surface morphology of the modified CF after brush coating with HD I;

[0033] Figure 8 Shown is the SEM surface morphology of the modified PMMA after brushing HD I;

[0034] Fig. 9 Shown is a process flow chart for improving the CF / PMMA interface bonding performance. DETAILED DESCRIPTION

[0035] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0036] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present invention. As used herein, unless otherwise explicitly stated in the present invention, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "include" and / or "include" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof;

[0037] This embodiment provides a method for modifying the interface of a carbon fiber reinforced thermoplastic resin-based composite material, which improves the mechanical properties of the interface of the fiber reinforced thermoplastic resin-based composite material by grafting the surface of the material, performs surface modification on carbon fiber (CF) and polymethyl methacrylate resin (PMMA), introduces active carboxyl groups on the surface of the material, and then uses hexamethylene diisocyanate (HDI) as a coupling layer to connect the carboxyl groups on the surface of the carbon fiber and polymethyl methacrylate resin to form a "molecular bridge", thereby enhancing the interfacial bonding force between the resin and the fiber by chemical grafting. A modified carbon fiber reinforced polymethyl methacrylate composite material sample (CF / PMMA) was prepared by a thin film lamination method, and a microscopic verification test was performed on the prepared composite material sample to verify the effectiveness of the method proposed by the present invention, laying a foundation for the wide application of fiber reinforced thermoplastic resin-based composite materials, and specifically includes the following steps:

[0038] A. Surface modification treatments were performed on carbon fiber and polymethyl methacrylate respectively. The purpose of the treatments was to introduce polar carboxyl groups on the resin and fiber surfaces, including:

[0039] 1) Prepare an appropriate amount of acidic potassium permanganate solution, immerse the cleaned carbon fiber in the prepared acidic potassium permanganate solution, soak for 1 to 5 hours, take out the carbon fiber, clean and dry it, and seal it for future use;

[0040] 2) Brush tetrahydrofuran on the surface of a cleaned polymethyl methacrylate film with a thickness of 0.1 to 0.5 mm, seal it and let it stand for 10 to 60 minutes, then take it out, and then soak it in a dilute hydrochloric acid solution for 1 to 5 hours. After the treatment, take it out, dry it, seal it and store it for later use;

[0041] B. Preparation of composite material specimens, including:

[0042] 1) Cut the processed polymethyl methacrylate film sheet with a thickness of 0.1 to 0.5 mm and the carbon fiber into appropriate sizes according to the mold size;

[0043] 2) Apply a layer of hexamethylene diisocyanate on the surface of the processed and cut fibers and resin films, apply evenly and lay them in the designed laying order to form a preform, so that the outermost layers of the upper and lower surfaces are both resin film sheets;

[0044] 3) Lay release cloth on the upper and lower surfaces of the preform, and then put it into a vacuum bag for vacuum treatment;

[0045] 4) The vacuumed and treated composite material preform is placed in a press molding mold with a working temperature of 100 to 250° C. and a working pressure of 2 to 20 MPa. After hot pressing for 1 to 3 hours, the mold is taken out and placed on a workbench for cooling. After cooling to room temperature, the demolding cloth is opened to obtain a modified carbon fiber reinforced polymethyl methacrylate composite material (CF / PMMA) sample.

[0046] C. Conduct microscopic verification tests on the composite material specimens prepared according to the above method, including:

[0047] 1) Fourier transform infrared spectrometer (FTIR) was used to analyze the surface functional group changes of carbon fiber before and after modification, polymethyl methacrylate before and after modification, carbon fiber after modification with the introduction of hexamethylene diisocyanate, and polymethyl methacrylate after modification with the introduction of hexamethylene diisocyanate, so as to determine whether chemical grafting is achieved between the resin and the fiber layer. The experiment was carried out in ATR mode with a scanning range of 400-4000cm -1 , the spectral resolution is 4 cm -1 , draw the obtained data into a chart;

[0048] 2) Use field emission scanning electron microscopy to observe the surface morphology of the material at each processing stage and analyze the changes in the microstructure.

[0049] The processing method in step A 1) comprises:

[0050] a. The acidic potassium permanganate aqueous solution is a mixed solution prepared by using deionized water with a mass fraction of 5 to 30% and adding an appropriate amount of dilute hydrochloric acid with a concentration of 0.01 to 1 mol / L. Potassium permanganate is a common strong oxidant with the strongest oxidizing property under acidic conditions and will not damage the surface structure of the material;

[0051] b. The immersion process is carried out in an ultrasonic cleaner at a water bath temperature of 10 to 60°C;

[0052] c. The cleaning and drying method of carbon fiber is to wash the surface of carbon fiber four times with deionized water, and then put the cleaned carbon fiber into a preheated oven for drying for 10 to 50 minutes.

[0053] The processing in step A 2) includes:

[0054] a. Polymethyl methacrylate can be dissolved by tetrahydrofuran, and after partially dissolving the surface of the film, it can better react with hydrochloric acid to generate polar group carboxyl;

[0055] b. The concentration of the hydrochloric acid solution used is 0.01 to 1 mol / L;

[0056] c. The soaking process is carried out in an oven with an internal temperature of 10 to 60°C.

[0057] The purpose of using hexamethylene diisocyanate as the intermediate medium in step B 2) is that both ends of the hexamethylene diisocyanate molecule have polar -NCO groups, which can react chemically with the carboxyl groups on the fiber and the resin, respectively, to connect the two materials well and achieve chemical grafting. The molecular structure of hexamethylene diisocyanate is as follows:

[0058]

[0059] The following is combined with Figures 1 to 9 The process of implementing the present invention is further illustrated by the results of microscopic tests.

[0060] 1. Microscopic principle analysis:

[0061] like Figure 1 As shown in the figure, both ends of the HDI molecular chain have polar -NCO groups. Based on this special molecular structure, HDI is used as an intermediate medium to connect the fiber and the resin interface. Figure 2 As shown in the figure, after the surface modification of the fiber and resin, -COOH groups were introduced on the surface of the materials, which reacted with the -NCO polar groups at both ends of HDI to form a chemical bond between the materials. Figure 2 Where O and P represent the chemical reaction between -NCO group and -COOH group respectively as shown below:

[0062] R-NCO+R′-COOH→R-NH-COR′→+CO2

[0063] 2. Composite material modification and preparation process:

[0064] 1). CF, PMMA surface modification:

[0065] The carbon fiber used in this implementation process is a carbon fiber woven cloth, which is prepared with 1L of a 20% potassium permanganate aqueous solution and 10mL of a 0.1mol / L dilute hydrochloric acid mixed solution. Potassium permanganate is a common strong oxidant, which has the strongest oxidizing property under acidic conditions and will not seriously damage the surface structure of the material. Pour the prepared acidic potassium permanganate solution into the SCQ-1020B ultrasonic cleaner, immerse the cleaned carbon fiber into the prepared acidic potassium permanganate solution, set the water bath temperature to 40°C, take out the carbon fiber after ultrasonic immersion for 4 hours, wash the carbon fiber with deionized water, and then put it into an oven for drying and sealing for storage;

[0066] Tetrahydrofuran was brushed on the surface of a clean 0.2 mm thick polymethyl methacrylate film, sealed and allowed to stand for 30 minutes before being taken out, and then the film was immersed in a 0.1 mol / L dilute hydrochloric acid solution, and then placed in an oven at 45°C for 3 hours. After the treatment, it was taken out, dried, sealed and stored for later use.

[0067] 2). Preparation of composite materials:

[0068] The processed polymethyl methacrylate film sheets with a thickness of 0.2 mm and the carbon fiber woven cloth are cut into 15 cm*15 cm squares, the carbon fiber woven cloth is cut into 4 pieces, and the polymethyl methacrylate film sheets are cut into 5 pieces; a layer of hexamethylene diisocyanate with a thickness of 0.025 mm is applied on the surface of the cut fiber and resin film, and after evenly applied, they are laid in the designed layering order to form a preform, such as Figure 3 shown.

[0069] Lay release cloth on the upper and lower surfaces of the preform, and then put it into a vacuum bag for vacuum treatment;

[0070] The vacuumed and processed composite material preform is placed in a square hollow mold of the same size, and the press molding working temperature is set to 170°C and the working pressure is set to 10MPa. After the temperature reaches 170°C, the mold is put into hot pressing for 1 hour, and then the mold is taken out and placed on the workbench to cool. After cooling to room temperature, the demolding cloth is opened to obtain a carbon fiber reinforced polymethyl methacrylate composite material CF / PMMA sample.

[0071] 3. Micro testing:

[0072] 1). FTIR spectrum analysis:

[0073] The above invention principle and process method can be verified by microscopic experiments, as shown in the spectrum of FIG4 , and the specific verification analysis is as follows:

[0074] FTIR was used to characterize the chemical groups on the surface of CF and PMMA at each treatment stage to analyze whether new chemical bonds were generated. Figure 4(a) shows the infrared spectra of CF before and after modification with acidic potassium permanganate solution; Figure 4(b) shows the infrared spectra of PMMA film before and after modification with HCl solution; Figure 4(c) shows the infrared spectra of CF and PMMA before and after modification with HDI. In the spectrum curve u of Figure 4(a), 1625cm -1 The C=O stretching vibration peak in the carboxyl group is 3251 cm -1 The peak at 1630cm is the stretching vibration peak of OH in the carboxyl group. Compared with curve v, it can be inferred that carboxyl groups exist on the surface of CF after oxidation modification with KMnO4 solution. -1The C=O stretching vibration peak in the carboxyl group is 3300 cm -1 The peak at 761 cm is the stretching vibration peak of OH in the carboxyl group. Compared with the curve x, it can be inferred that the carboxyl group exists on the surface of PMMA after hydrolysis and modification by HCl solution. In the spectrum curves y and z of Figure 4 (c), 761 cm -1 and 1533cm -1 The NH bending vibration peak of the amide group is 1678 cm -1 The C=O stretching vibration peak in the amide group is 3328 cm -1 The peak at the center is the NH stretching vibration peak in the amide group, and the peaks of the two curves are basically consistent. The changes in these characteristic peaks can be inferred that HDI has chemically reacted with the modified CF and the modified PMMA to form a new identical chemical group, the amide group.

[0075] 2). Scanning electron microscope SEM micrograph:

[0076] Figure 5(a) shows the untreated carbon fiber with a smooth and neat surface; Figure 5(b) shows the surface morphology of the CF after oxidation with an acidic potassium permanganate solution. The roughness is significantly improved, and a certain degree of etching marks appear on the surface, indicating that the surface of the carbon fiber is slightly damaged after being immersed in an acidic potassium permanganate solution, and the friction between the resin and the fiber is increased to a certain extent through physical modification.

[0077] Figure 6(a) and 6(b) This is the microscopic morphology of the PMMA surface before and after hydrolysis treatment. After treatment, the surface becomes rough and obvious etching marks appear. Figure 7 , Figure 8 The microscopic morphologies of the modified CF and PMMA surfaces coated with HD I are shown in the figure. It can be seen from the figure that HD I is tightly attached to the surfaces of the two materials. Through infrared spectroscopy analysis, it can be determined that CF and PMMA form a chemical connection bond under the action of HD I.

[0078] The present invention proposes a complete set of flow charts for improving the interface mechanical properties of carbon fiber reinforced polymethyl methacrylate composite materials using hexamethylene diisocyanate as shown in the following figure: Fig. 9 As shown, the process was used to successfully produce carbon fiber thermoplastic resin matrix composite specimens, which have excellent interface bonding properties.

Claims

1. A method for modifying the interface of a carbon fiber reinforced thermoplastic resin-based composite material, characterized in that The following method steps: 1) Prepare an acidic potassium permanganate solution, immerse the cleaned carbon fiber in the prepared acidic potassium permanganate solution, and under the oxidation of the acidic potassium permanganate solution, carboxyl groups appear on the surface of the carbon fiber. After soaking for a set time, take out the carbon fiber, clean and dry it, and seal it for storage; 2) Brush tetrahydrofuran on the surface of the cleaned polymethyl methacrylate film, seal it and let it stand, then take it out, and then soak it in a dilute hydrochloric acid solution for a set time. After the treatment, take it out, dry it, seal it and store it for later use; 3) cutting the processed polymethyl methacrylate film and carbon fiber into appropriate sizes according to the size of the mold; 4) Apply a layer of hexamethylene diisocyanate on the surface of the processed and cut fibers and resin films, apply evenly, and lay them in the designed laying order to form a preform, so that the outermost layers of the upper and lower surfaces of the preform are both resin film sheets; 5) Lay release cloth on the upper and lower surfaces of the preform, and then put it into a vacuum bag for vacuum treatment; 6) placing the vacuumed and treated composite material preform into a press molding die at a set temperature and a set pressure, taking out the mold after hot pressing for a set time and placing it on a workbench to cool, and opening the demoulding cloth after cooling to room temperature to obtain a modified carbon fiber reinforced polymethyl methacrylate composite material sample; In the step 2), the polymethyl methacrylate can be dissolved by using tetrahydrofuran, and after the surface of the film is partially dissolved, it can be better hydrolyzed with hydrochloric acid to generate polar group carboxyl; In the step 4), both ends of the hexamethylene diisocyanate molecule have polar -NCO groups, which can chemically react with the carboxyl groups on the fiber and the resin respectively, so as to well connect the two materials and realize chemical grafting.

2. The method for modifying the interface of a carbon fiber reinforced thermoplastic resin-based composite material according to claim 1, characterized in that: The acidic potassium permanganate solution in step 1) is a mixed solution prepared by using deionized water with a mass fraction of 5 to 30% and adding an appropriate amount of dilute hydrochloric acid with a concentration of 0.01 to 1 mol / L.

3. The method for modifying the interface of a carbon fiber reinforced thermoplastic resin-based composite material according to claim 1, characterized in that: The immersion process described in step 1) is carried out in an ultrasonic cleaner with a water bath temperature of 10 to 60°C.

4. The method for modifying the interface of a carbon fiber reinforced thermoplastic resin-based composite material according to claim 1, characterized in that: The cleaning and drying method of the carbon fiber is to clean the surface of the carbon fiber four times with deionized water, and put the cleaned carbon fiber into a preheated oven for drying for a set time.

5. The method for modifying the interface of a carbon fiber reinforced thermoplastic resin-based composite material according to claim 1, characterized in that: The concentration of the hydrochloric acid solution used in step 2) is 0.01-1 mol / L.

6. The method for modifying the interface of a carbon fiber reinforced thermoplastic resin-based composite material according to claim 1, characterized in that: The soaking process in step 2) is carried out in an oven with an internal temperature of 10-60°C.

Citation Information

Patent Citations

  • Composite membrane material and preparation method thereof

    CN114457580A

  • Surface modified high strength fiber and manufacturing method therefor, resin composition and manufacturing method therefor

    JP2019127555A